School Principal Innovation As A Strategy In Establishing Students' Religious Culture - Badrus Soleh; Nurul Azizah; Abd. Halik (The Faculty of Education and Teaching Training, 2023)
This research aims to describe the principal’s innovation as a strategy in establihing the religious culture of students at Junior High School Larangan Pamekasan. This research used descriptive qualitative methods. Data was obtained through interviews, observation and documentation. The validity of the data was checked through through extended observations, persistence of observations, and triangulation. The results of this research are: First, the principal’s innovation as a strategy in establishing the religious culture of students at SMPN 1 Larangan Pamekasan is implemented through the development of character education innovation activities, such as Ya Habibi program which contains some activities like Yasin recitation, memorizing Al-Qur’an, and qiroah mentoring. Second, the implementation of the principal’s innovation as a strategy in establishing the religious culture of students at SMPN 1 Larangan Pamekasan was carried out at different times; yasing recitation was done daily, memorizing Al-Qur’an and qiroah mentoring were done weekly. Third, the evaluation within the principal’s innovation as a strategy in establishing the religious culture of SMPN 1 Larangan Pamekasan students was done through regular evaluation meetings as well as accountability reports from the person in charge of Ya Habibi program carried out once a month, as well as follow-up assessments by looking at the potential of student from Ya Habibi program by involving students in school events, as well as various kinds of competitions related to Ya Habibi activities. Penelitian ini dilakukan karena memiliki tujuan untuk mendeskripsikan inovasi kepala sekolah sebagai strategi dalam membangun budaya religius siswa SMPN 1 Larangan Pamekasan. Penelitian ini menggunakan metode kualitatif deskriptif. Data diperoleh melalui cara wawancara, observasi, dan dokumentasi. Pengecekan keabsahan data dilakukan melalui perpanjangan pengamatan, ketekunan pengamatan, dan triangulasi. Adapun hasil dari penelitian ini yaitu: Pertama, inovasi kepala sekolah sebagai strategi dalam membangun budaya religius siswa SMPN 1 Larangan Pamekasan dilaksanakan melalui kegiatan pengembangan kegiatan inovasi pendidikan karakter, yaitu program Ya Habibi yang memuat tiga kegiatan didalamnya, yaitu pembacaan Yasin, hafalan Al-Qur’an dan bimbingan qiroah. Kedua, implementasi inovasi kepala sekolah sebagai strategi dalam membangun budaya religius siswa SMPN 1 Larangan Pamekasan melalui kegiatan Ya Habibi dilaksanakan dalam waktu yang berbeda, yaitu setiap hari untuk pembacaan yasin, dan satu minggu sekali untuk hafalan Al-Qur’an dan bimbingan qiroah. Ketiga, evaluasi inovasi kepala sekolah sebagai strategi dalam membangun budaya religius siswa SMPN 1 Larangan Pamekasan melalui kegiatan Ya Habibi, melalui rapat evaluasi rutin sekaligus laporan pertanggungjawaban dari penanggungjawab kegiatan Ya Habibi yang dilaksanakan setiap satu bulan satu kali, serta penilaian tindak lanjut dengan melihat potensi siswa anggota program Ya Habibi dengan turut mengikut sertakan siswa pada acara-acara sekolah, serta berbagai macam perlombaan yang memiliki keterkaitan dengan kegiatan Ya Habibi.